ISLAMIC BANKING AND BANK PERFORMANCE IN MALAYSIA: AN EMPIRICAL ANALYSIS - Mansor H. Ibrahim (Bank Indonesia, 2020)
This paper examines the performance of Malaysia’s banking sector and its relationship to the presence of Islamic banking in the country. More specifically, by controlling for the theoretically relevant determinants of bank performance we compare the efficiency, profitability and risk of Islamic banks to conventional banks and examine the spillover effects of Islamic banking penetration on bank performance. To these ends, we adopt a panel modelling approach. Taking note that our focal variables comprise the time-invariant Islamic banking dummy and potentially endogenous Islamic banking share, we apply the Hausman–Taylor (HT) instrumental-variable estimator in the analysis. Our results indicate that Islamic banks in Malaysia are less profitable than their conventional counterparts and that Islamic banking penetration is associated with lower bank profitability. However, the increasing presence of Islamic banking appears to make Malaysian banks less risky and, with limited evidence, more efficient. Finally, the efficiency–risk trade-off seems to have potential as the Islamic banking portion of the sector increases in size. These results are reasonably robust compared to alternative specifications of the model.